The Impossibility of Meaning: Joining and Rejoining: Reply to Cooney, Ferro, and Stern. Issue 2 (3rd March 2020) - McGleughlin, Jade
Abstract : In response to commentaries on my paper The Analyst's Necessary Nonsovereignty and the Generative Power of the Negative, by Donnel B. Stern, Antonino Ferro, and Amy Schwartz Cooney (this issue), I grapple with queries including defining subjectivity and sovereignty (Cooney); the negative in relation to subjectivity (Stern); the power and problematic nature of the analyst as both part of the field and interpreter of the field (Ferro); and the asymmetry of the analyst/patient relationship. More significantly I return to my own emphasis on knowing as assurance and wonder how our writing may engage less sovereignty and include more performance, play, risk and vulnerability. I query what we achieve when knowing is interrupted by the negative and suggest a shared sensory experiencing may allow access to a transformational process where the force of the negative runs through us all.